PERSEPSI AUDITOR TERHADAP PENGHENTIAN PREMATUR (PREMATURE SIGN OFF) ATAS PROSEDUR AUDIT YANG DIKAITKAN DENGAN TIME BUDGET PRESSURE (STUDI PADA AUDITOR PEMERINTAH DI KOTA BANDA ACEH) - Nita Erika Ariani; Maya Febrianty Lautania (Jurnal Telaah dan Riset Akuntansi, 2008)
This study is aimed to knowing the sequence of audit procedure which most often signed off in time pressure condition.  Samples were selected by using random sampling method. From 119 questionnaires that have been distributed, there were 61 questionnaires returned and these were used as the research samples. This study was analyzed by using Friedman test to determinated the priority of discontinued audit procedures.     The result of this research indicates that there are priority sequence of discontinued audit prosedure in time pressure condition by governmental auditor in Banda Aceh. The most audit prosedure which  often to be left  is understanding business’s client. Then the following of sequence audit prosedure are control prosedure on on-line transaction aplication system, Confirmation, Reduced in samples, Internal auditor judgement, Subtantive test, Client internal control judgment, analitical prosedures, using management representative and audit prosedure which seldom to be left is physical examination.     The sugest of next research is to study at difference location and the classification of auditor based on how long time they have been work as auditor, so we can compare the auditor behavior between senior and junior auditor. Keyword : Premature Sign Off, Audit Prosedures, Government Auditor